2021
DOI: 10.3390/su13052995
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Model of the Relationship between Miners’ Work Commitment, Cultural Emotion and Unemployment Risk Perception

Abstract: The psychological health and work commitment of miners are prerequisites to ensuring their sustainable safety behavior, and it is also significant to the sustainable development of coal mines in China. In this context, we conducted a questionnaire survey among coal miners of state-owned coal enterprises to explore the relationships between cultural emotion, unemployment risk perception, Big Five personality traits, and work commitment. The results reveal that (1) cultural emotion and its three dimensions playe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…This view was also supported by [22]. In a very recent study on mineworker commitment, [23] established that cultural emotion and its dimensions played a significant positive role in promoting work commitment. Along with other factors such as teamwork, adaptability, promotion, etc., studies have established that a friendlier work environment, rewards and recognition systems that encourage, and institutional policies that are fairly and equally applied to all are associated with higher commitment of staff and a greater the intention to stay [15,24,25].…”
Section: Institutional Sustainabilitymentioning
confidence: 83%
“…This view was also supported by [22]. In a very recent study on mineworker commitment, [23] established that cultural emotion and its dimensions played a significant positive role in promoting work commitment. Along with other factors such as teamwork, adaptability, promotion, etc., studies have established that a friendlier work environment, rewards and recognition systems that encourage, and institutional policies that are fairly and equally applied to all are associated with higher commitment of staff and a greater the intention to stay [15,24,25].…”
Section: Institutional Sustainabilitymentioning
confidence: 83%
“…Meanwhile, for assessing Job satisfaction, we use an adapted questionnaire from (Ramli, 2019;Vorina et al, 2017). On another side, we use a questionnaire adapted from (Li et al, 2021;Reddy et al, 2019) for a variable work commitment.…”
Section: Discussionmentioning
confidence: 99%
“…It is found that the unemployment risk perception is composed of psychological, financial, relationship, citizenship and re-immigration. Yonghui L et al combined with the Chinese context, the perception of unemployment risk is divided into three categories: policy unemployment risk perception, individual differential unemployment risk perception and technical unemployment risk perception [7].…”
Section: Foreign Literature Reviewmentioning
confidence: 99%